The Influence of Attitude and SubjectiveNorm Towards The Purchase Intention as Potential Consumer of Mouthwash Product - Fea Prihapsara; Rosyta Velayanti (Universitas Sebelas Maret, 2017)
Mouthwash is used by some people to maintain oral hygiene in order to avoid the interference of oral cavity diseases. Theory of Reasoned Action (TRA) is a theory measuring the influence of behavioral and subjective norm regarding someone’s perception toward the purchase intention. The objective of this research is to analyze the influence of attitude and subjective norm both partially and simultaneously towards the purchase intention of mouthwash potential consumer.This study is non-experimental descriptive research with the survey method and data collection carried out by cross sectional by using judgemental sampling technique. The population of this research is all of Surakarta society which has been using mouthwash in six month untill March 2013 as the research subject. There are 120 respondents in this research. Data analysis using multiple linier regression to determine the influenceof attitudeand subjective norm towards the purchase intention.The result of the research shows that consumers attitudepartiallyinfluences toward mouthwash purchase intention (t-value 0,000), subjective norm partially influences toward mouthwash purchase intention (t-value 0,038), and attitude and subjective norm simultaneouslyinfluence toward mouthwash purchase intention that is 36,5% (F-value 0,000).